Views of parents of children with sickle cell disease on pre‐implantation genetic diagnosis. Issue 8 (18th April 2018) - Darbari, Isha; O'Brien, Jeanne E.; Hardy, Steven J.; Speller‐Brown, Barbara; Thaniel, Lisa; Martin, Brenda; Darbari, Deepika S.; Nickel, Robert S.
Abstract: Pre‐implantation genetic diagnosis (PGD) is an option for parents who have a child with sickle cell disease (SCD) to have another child without SCD. We conducted a survey of 19 parents with at least one child with SCD to investigate views on PGD. Before education, 44% of parents were aware of PGD. All parents rated PGD education as important. All parents considering another child also reported interest in using PGD if insurance covered its costs. Parents who have a child with SCD appear to be interested in PGD and educational tools informing this group about PGD should be developed.